New insights into the functional roles of reactive oxygen species during embryo sac development and fertilization in Arabidopsis thaliana - Martin, María Victoria (2013)
Previously considered as toxic by-products of aerobic metabolism, reactive oxygen species (ROS) are emerging as essential signaling molecules in eukaryotes. Recent evidence showed that maintenance of ROS homeostasis during female gametophyte development is crucial for embryo sac patterning and fertilization. Although ROS are exclusively detected in the central cell of mature embryo sacs, the study of mutants deficient in ROS homeostasis suggests that controlled oxidative bursts might take place earlier during gametophyte development. Also, a ROS burst that depends on pollination takes place inside the embryo sac. This oxidative response might be required for pollen tube growth arrest and for sperm cell release. In this mini-review, we will focus on new insights into the role of ROS during female gametophyte development and fertilization. Special focus will be made on the mitochondrial Mn-Superoxide dismutase (MSD1), which has been recently reported to be essential for maintaining ROS homeostasis during embryo sac formation.